Fémhabstruktúrák elemzése és geometriai modellezése - Varga, Tamás Antal; Mankovits, Tamás (International Journal of Engineering and Management Sciences, 2016)
The development of an efficient procedure for 3D modelling and finite element simulation of metal foams is one of the greatest challenges to engineer researchers nowadays. Creating 3D CAD model is alone a demanding engineering task due to its extremely complex geometry, and the proper finite element analysis process is still in the center of the research. The aim of this project is to analyze the related literature and to adapt the results may be considered